The Role Of Regulations In Supporting The Restoration Of Mangrove Ecosystems For The Achievement Of Sustainable Development Goals: A Literature Review - Ika Dian Anggraeni (Eduvest - Journal of Universal Studies, 2024)
Mangrove ecosystems, among the world's most productive environments, provide critical ecological, economic, and social benefits while supporting Sustainable Development Goals (SDGs). However, these ecosystems face degradation due to deforestation, land conversion, pollution, and climate change. This study examines the pivotal role of regulations in mangrove restoration to achieve the SDGs, utilizing case studies from Indonesia and Thailand. It highlights successful regulatory frameworks, such as the implementation of Social Forestry policies in East Kalimantan and the Regional Regulation in Maros Regency, South Sulawesi. These frameworks integrate social, economic, and ecological pillars to promote sustainable mangrove management. By analyzing regulatory contributions to SDGs 6, 13, 14, and 15, this research emphasizes ecosystem-based management, community involvement, and international compliance as fundamental elements for effective restoration. The findings demonstrate that well-designed regulations can harmonize environmental protection with economic development, offering actionable insights for policymakers and stakeholders to ensure mangrove ecosystem sustainability.